P489 Temporal trends of colectomy for ulcerative colitis in the multi-drug era; a population based cohort study. (21st January 2022) - Jenkinson, P; Plevris, N; Lyons, M; Gros, B; Derikx, L; Constantine-Cooke, N; Jones, G; Lees, C
Abstract: Background: We are now in the multi-drug era for ulcerative colitis (UC). The use of advanced therapies for UC has dramatically increased over the last 6 years. NICE approvals of anti-TNF and anti-α4β7 therapy (both in 2015) were followed by IL12/23 (2019) and janus kinase inhibitors (2020). The aim of this study was to describe the impact of this change in patterns of advanced therapy prescribing on colectomy rates for UC within a well defined population-based cohort. Methods: The Lothian IBD registry (LIBDR) is a manually validated, prevalent dataset compiled through capture-recapture methodology (Jones et al. 2018) that is >95% complete for the 907, 580 residents of NHS Lothian (mid-2019 population estimates). The LIBDR contains measured prevalence between 2008–2018, estimated prevalence from 2018–2028 (derived from Autoregressive integrated moving average ARIMA modelling). All patients with a diagnosis of UC who underwent a colectomy in Lothian, Scotland between 01/01/2005 and 31/102021 were identified by interrogating multiple clinical and administrative databases. Linear and segmental regression analyses were used to identify the annual percentage change (APC) and temporal trends (statistical joinpoints) in colectomy rates. Results: 485 patients underwent colectomy for UC between 2005 and October 2021 (Fig 1). Colectomy rates per 100 UC patients fell from 1.47 colectomies in 2005 to 0.25 in 2021 (p=0.009). The colectomy APC decreased by 4.1% per year between 2005 and 2014 and 18.5% per year between 2014 and 2021 (Figure 2). Temporal trend analysis (2005–2021) identified a significant joinpoint in colectomy rates in 2014 (p=0.009) (Figure 2). Figure 1 Absolute number of colectomies for UC per year between 2005–2021. Linear regression showing colectomy numbers (solid line) and 95% confidence intervals (dashed lines) constrained at 2014. Figure 2, Colectomy rates per 100 UC patients from 2005–2021. Joinpoint regression separated at inflection point at 2014 (solid line). Between 2005 and 2007, 0 / 100 patients undergoing colectomy received maintenance biologic treatment prior to the admission for colectomy. Between 2019 and 2021, 19 / 33 (57.8%) patients received maintenance biologic therapy prior to colectomy (Figure 3). Figure 3. Percentage of colectomy patients who had been treated with at least 1 maintenance biologic prior to surgery. Conclusion: This population based cohort study has shown a significant reduction in the rate of colectomy for UC that has coincided with the introduction of biologic medication. Whilst we cannot ascribe causality, within this study the timeline of falling colectomy rates closely parallels the rapid increase in the use of biologic medication.